Restoring rational choice: The challenge of consumer financial regulation - John Y. Campbell (European Central Bank (ECB), 2016)
This lecture considers the case for consumer financial regulation in an environment where many households lack the knowledge to manage their financial affairs effectively. The lecture argues that financial ignorance is pervasive and unsurprising given the complexity of modern financial products, and that it contributes meaningfully to the evolution of wealth inequality. The lecture uses a stylized model to discuss the welfare economics of paternalistic intervention in financial markets, and discusses several specific examples including asset allocation in retirement savings, fees for unsecured short-term borrowing, and reverse mortgages.
Keywords: D12; D18; G28; 330; consumer protection; financial literacy; wealth inequality